KEBIJAKAN INDONESIA DALAM PERLINDUNGAN PEKERJA MIGRAN INDONESIA MELALUI SISTEM PENEMPATAN SATU KANAL (SPSK) DI ARAB SAUDI TAHUN 2018-2023 - Hartono, Iqlima Hibatillah; Retnaningsih, Umi Oktyari (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2025)
This study analyzes how the One Channel Placement System (SPSK) policy can help provide protection to Indonesian Migrant Workers (PMI) in Saudi Arabia. The country is the main destination for PMI, but the high number of complaints of violence and exploitation demands a stronger protection system. SPSK is a digital-based policy with a guaranteed recruitment process and was born through the signing of a Memorandum of Understanding (MoU) between Indonesia and Saudi Arabia in 2018 and is specifically intended for domestic migrant workers. This study uses a qualitative method with data collection techniques through document studies sourced from BP2MI, academic books, journals, articles, reports of related organizations, and other official documents. This study also uses a Liberalism perspective with a framework of analysis and a State level of analysis. The results of this paper indicate that the SPSK successfully dispatched 100 migrant workers in the initial phase but still faced various obstacles, such as limited placement companies and unclear subsequent departure stages. The effectiveness of this policy was also hampered by a lack of technical clarity in the field. On the other hand, several non-governmental organizations, such as Suara Perempuan, Migrant Watch, and Migrant Care, criticized the weak implementation of this policy. In addition to technical issues, a fundamental weakness lies in the legal basis used, namely the MoU, which is not binding and does not include sanctions for violations. This study found that before implementing a policy like the SPSK, Indonesia should seek a legally binding bilateral agreement to ensure optimal and sustainable protection for migrant workers. Keywords: Indonesian Migrant Workers, One Channel System, Protection